Kepemimpinan Kepala Sekolah Perempuan: Studi di SMA N 1 Ulu Musi, EmpatLawang Sumatera Selatan - Muhammad Andhika; Trie Hartiti Retnowati; Toba Sastrawan Manik (Universitas Muhammadiyah Surakarta, 2021)
The purpose of this qualitative study is to find out how the leadership role of a female school headmaster in rural areas that is in SMAN 1 Ulu Musi, Empat Lawang Regency, Sumatera Selatan Province. This study is a qualitative research with a case study approach. Data collection techniques with in-depth interviews, participant observation, and document study. The informant in this study was the principal of SMA N 1 Ulu Musi. The result of this study found when women become headmaster in senior high school, gender is not an obstacle to undergoing the task of being the highest leader in a school. In fact, the leadership and managerial qualities of women from a headmaster of SMAN 1 Ulu Musi have a number of advantages such as being independent, having good communication, being democratic, being able to face a number of challenges and being willing to work with the team. However, there are also some shortcomings of a female leader, especially at the principal of SMAN 1 Ulu Musi, which tends to involve feelings, order subordinates unevenly, and sternly. This article will also explain some of the challenges she faced while serving as headmaster, actions taken, and hopes for various parties for the progress of SMAN 1 Ulu Musi. The components that must be fulfilled by a school headmaster are personality, managerial, entrepreneurship, supervision and social. This research implies that female gender has its own advantages that can actually advance a school.